Analisis Perilaku Strukur Gedung Ditinjau Dari Jarak Dilatasi (Studi Kasus : Gedung Kejaksaan Purwokerto) - Ramadhani, Dennis; Wibowo, Mukti Agung; Azizi, Amris (Proceedings Series on Physical & Formal Sciences, 2026)
Dilation is a joint or separator in a building because it has different or irregular structural systems. This research aims to analyze the safe dilation distance to be used. The research uses a quantitative method with the aid of ETABS V.22 software to analyze building behavior in relation to expansion joint spacing. Based on the analysis, the inter-story drift values for Building 1 are X = 38.020 mm and Y = 49.910 mm; for Building 2, X = 35.977 mm and Y = 49.457 mm; and for Building 3, X = 39.629 mm and Y = 46.015 mm. These inter-story drifts for the three structures indicate compliance with the drift limits stipulated by SNI 1726-2019, as all values are well below the maximum allowable limit of 80 mm. The required expansion joint distances to accommodate seismic loads are calculated as follows: 87.930 mm for Building 1, 85.434 mm for Building 2, and 85.644 mm for Building 3. As all calculated distances remain below the 100 mm safety threshold, the planned expansion joints are deemed safe, with no anticipated collision between separated structures during seismic activity.